Enhancing Customer Awareness of Cybersecurity Threats in E-Banking: A Study on the Role of AI-based Risk Communication Tools - Hakimi, Musawer; Kohistani, Ahmad Jamy; Sahnosh, Faqeed Ahmad; Samadzai, Abdul Wahid; Enayat, Wahidullah (Universitas Pendidikan Nasional, 2025)
With online banking on the rise, cybersecurity issues still occupy users' and financial institutions' minds. This study examines users' awareness of cybersecurity threats and their trust in artificial intelligence (AI) technology for fraud detection and risk communication in e-banking. A mixed-method design of quantitative survey of 384 users and qualitative interview of 20 participants was used to reflect broader insights. The survey quantified demographics, awareness of security protocols, and confidence in AI technology. Findings show that while users are very well aware of what to anticipate from repeated online threats and are careful with login passwords, they always fail to take the initiative concerning security practices like the changing of passwords. Overall, participants were confident in the application of AI systems, especially the efficiency and pace at which AI identifies fraud versus human agents. Skepticism was found for the effectiveness of chatbots based on AI. Statistical modeling showed that trust in AI strongly correlated with prior experience in cybersecurity, high rates of technology usage, and knowledge of online banking, with education level and age making little impact. The qualitative information further underscored the importance of personalized and clear communication from AI systems, suggesting that the way such machines talk to individuals can make or break trust. The study concludes by suggesting that user education at financial institutions should be enhanced, as well as developing AI systems with a method that employs personal communication approaches. The integration of human support with AI can potentially plug awareness gaps and improve security results across different user segments within the e-banking environment.